Milk decreases urinary excretion but not plasma pharmacokinetics of cocoa flavan-3-ol metabolites in humans - Mullen, W.; Borges, G.; Donovan, J.; Edwards, Christine; Serafini, M.; Lean, M.; Crozier, A. (American Society for Nutrition, 2009)
Background: Cocoa drinks containing flavan-3-ols are associated with many health benefits, and conflicting evidence exists as to whether milk adversely affects the bioavailability of flavan-3-ols. Objective: The objective was to determine the effect of milk on the bioavailability of cocoa flavan-3-ol metabolites. Design: Nine human volunteers followed a low-flavonoid diet for 2 d before drinking 250 mL of a cocoa beverage, made with water or milk, that contained 45 µmol (-)-epicatechin and (-)-catechin. Plasma and urine samples were collected for 24 h, and flavan-3-ol metabolites were analyzed by HPLC with photodiode array and mass spectrometric detection. Results: Milk affected neither gastric emptying nor the transit time through the small intestine. Two flavan-3-ol metabolites were detected in plasma and 4 in urine. Milk had only minor effects on the plasma pharmacokinetics of an (epi)catechin-O-sulfate and had no effect on an O-methyl-(epi)catechin-O-sulfate. However, milk significantly lowered the excretion of 4 urinary flavan-3-ol metabolites from 18.3% to 10.5% of the ingested dose (P = 0.016). Studies that showed protective effects of cocoa and those that showed no effect of milk on bioavailability used products that have a much higher flavan-3-ol content than does the commercial cocoa used in the present study. Conclusions: Most studies of the protective effects of cocoa have used drinks with a very high flavan-3-ol content. Whether similar protective effects are associated with the consumption of many commercial chocolate and cocoa products containing substantially lower amounts of flavan-3-ols, especially when absorption at lower doses is obstructed by milk, remains to be determined. © 2009 American Society for Nutrition.